The Effect of SMK3 Implementation and Organizational Culture on Performance with K3L Certification as an Interventional Variable Indistribution Employee at PT PLN (Persero) UID North Sumatera - Muhammad Zein Nasution; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aims to investigate how the implementation of the Occupational Safety and Health Management System (SMK3) and corporate culture affects employee performance, with K3L Certification as an intermediary factor in the Distribution Division of PT PLN (Persero) UID North Sumatra. A quantitative method was employed, using a questionnaire for data collection. The study sample consisted of 163 employees, selected through a saturated sampling method. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that the implementation of SMK3 and corporate culture has a positive and significant impact on employee performance. Furthermore, both factors were shown to have a positive and significant effect on K3L Certification. Furthermore, K3L Certification significantly influences employee performance and acts as a mediating factor in the relationship between SMK3 implementation, corporate culture, and employee performance. Therefore, improved employee performance can be achieved through the successful implementation of SMK3, strengthening corporate culture, and the ongoing promotion of K3L Certification.